1993
DOI: 10.1038/363069a0
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic N. glauca plants expressing bacterial virulence gene virF are converted into hosts for nopaline strains of A. tumefaciens

Abstract: Tumours are induced by Agrobacterium tumefaciens on a variety of plants. The virulence determinants of A. tumefaciens reside on a large tumour-inducing (Ti) plasmid. This plasmid carries two regions essential for tumour induction, namely the T region and the Vir region. During infection the T region is transferred to the plant cell, where it becomes stably integrated in one of the host chromosomes as T-DNA. Expression of T-DNA leads to the production of the plant hormones auxin and cytokinin, as well as to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 22 publications
1
59
0
Order By: Relevance
“…Cascales and Christie (14) recently demonstrated, in an elegant study using a T-DNA immunoprecipitation assay, that the coupling protein VirD4 is the first component of the T4SS to interact with the T-DNA͞VirD2 transfer intermediate. The VirE2 protein interacts at the cell poles of the bacterium with VirD4 (20), strongly supporting the model that VirD4 is the cytoplasmic component of the T4SS that sorts not only nucleoprotein complexes but also the effector proteins for translocation and that T4SS are actually committed protein translocation systems (21,22). Translocation of the effector proteins VirF, VirE2, and VirE3 is mediated by a C-terminal transport signal (13,20,23,24).…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…Cascales and Christie (14) recently demonstrated, in an elegant study using a T-DNA immunoprecipitation assay, that the coupling protein VirD4 is the first component of the T4SS to interact with the T-DNA͞VirD2 transfer intermediate. The VirE2 protein interacts at the cell poles of the bacterium with VirD4 (20), strongly supporting the model that VirD4 is the cytoplasmic component of the T4SS that sorts not only nucleoprotein complexes but also the effector proteins for translocation and that T4SS are actually committed protein translocation systems (21,22). Translocation of the effector proteins VirF, VirE2, and VirE3 is mediated by a C-terminal transport signal (13,20,23,24).…”
mentioning
confidence: 59%
“…According to a current model, T4SSs are dedicated protein translocation machines that have evolved to transfer also nucleoprotein complexes (4,21). The relaxase protein that is covalently bound to the 5Ј end of the ssDNA molecule is thought to possess the T4SS transport signal and thus act as a pilot for the complex.…”
Section: Virb͞d4-dependent Translocation Of Relaxase Proteins Vird2 Andmentioning
confidence: 99%
“…This list includes DNA apparently of any length as long as it contains a recognition site for processing by the VirD2 endonuclease (34), the non-self-transmissible IncQ plasmid RSF1010, most likely also as a single-stranded DNA-protein particle (4, 9, 52), the VirE2 single-stranded DNA-binding protein (7,14,35), and VirF, which functions as an important virulence factor for infection of certain plant species (40). Second, recent studies have shown that the T-complex transporter delivers DNA to many dicotyledonous and monocotyledonous plant species as well as to agrobacteria (3,25) and yeast (10,11,36) recipient cells.…”
mentioning
confidence: 99%
“…The host factor VBF may be the key to understanding why A. tumefaciens strains lacking the virF gene can still induce tumors on some plant species (Hooykaas et al, 1984;Melchers et al, 1990;Jarchow et al, 1991;Regensburg-Tuïnk and Hooykaas, 1993). In such plants, A. tumefaciens may exploit a host VBF-like protein during infection as an alternative to VirF.…”
Section: Involvement Of a Host F-box Protein In A Tumefaciens Infectionmentioning
confidence: 99%
“…As a subunit of SCF, VirF targets at least VIP1 and its associated VirE2 for proteasomal degradation . This VirF function appears important for the infection process, as mutations in the virF gene substantially reduce infection efficiency in many, but not all, hosts (Melchers et al, 1990;Regensburg-Tuïnk and Hooykaas, 1993;Schrammeijer et al, 2001). …”
Section: The a Tumefaciens F-box Protein Virfmentioning
confidence: 99%